The determinants of Capital Structure: a comparison between small-cap and large-cap US firms - Gembali, Ravi Raj (2018)
This paper empirically compares the determinants of Capital Structure choice between small-cap and large-cap US firms. Trade-Off and Pecking Order Theories formulate hypotheses which are tested to deduce whether theoretical predictions coincide with empirical analysis. Panel data focussing on US corporates from 1966 to 2017 is utilized in explaining the dynamic relationship associated with Leverage. Particularly, the speed of adjustment to an optimal Leverage ratio, Size, Profitability, Tangibility, Growth, Non-Debt Tax Shields, Liquidity, and Volatility are investigated.